PENYULUHAN HUKUM TENTANG PERLINDUNGAN HUKUM DAN PENCEGAHAAN TERHADAP PENIPUAN INVESTASI ONLINE - Meirza Aulia Chairani; Krista Yitawati; Sarjiyati; Sigit Sapto Nugroho (Universitas Merdeka Madiun, 2022)
Abstract— This legal counseling aims to carry out the tridharma obligation, namely community service where we conduct legal counseling about legal protection and prevention of online investment fraud. The method used is to conduct a survey to the target community and conduct socialization and education directly to the community. This counseling educates about forms of legal protection for victims of online investment fraud, namely preventive and repressive legal protection and prevention strategies so that people do not become victims of online investments by educating people to be smart in choosing and sorting safe investments. On the one hand, investment provides forgiveness for improving the economy and on the other hand, if you place the wrong investment, it will result in losses to consumers. This legal counseling will provide education on which investments are legal and protected by the OJK and which ones are not. Provide legal assistance to victims who have been affected by fraudulent investments and how to resolve them so that the money and perpetrators of these fraudulent investments can be caught and will not harm other people.